DNA- and RNA-Binding Proteins Linked Transcriptional Control and Alternative Splicing Together in a Two-Layer Regulatory Network System of Chronic Myeloid Leukemia - Wang, Chuhui; Zong, Xueqing; Wu, Fanjie; Leung, Ricky Wai Tak; Hu, Yaohua; Qin, Jing (Frontiers in Molecular Biosciences, 2022)
DNA and RNA binding proteins (DRBPs) typically possess multiple functions to bind both DNA and RNA and regulate gene expression from more than one level. They are controllers for post-transcriptional processes such as splicing, polyadenylation, transportation, translation, and degradation of RNA transcripts in eukaryotic organisms, as well as regulators on the transcriptional level. Although DRBPs are reported to play critical roles in various developmental processes and diseases, it is still unclear how DRBPs work with DNAs and RNAs simultaneously and regulate genes at both transcriptional and post-transcriptional levels. To investigate the functional mechanism of DRBPs, we collected data from a variety of databases and literature and identified 118 DRBPs, which function as both transcription factors (TFs) and splicing factors (SFs), thus called DRBP-SF. Extensive investigations were done on 4 DRBP-SFs that highly expressed in chronic myeloid leukemia (CML), heterogeneous nuclear ribonucleoprotein K (HNRNPK), heterogeneous nuclear ribonucleoprotein L (HNRNPL), non-POU domain-containing octamer-binding protein (NONO), and TAR DNA-binding protein 43 (TARDBP). By integrating and analyzing ChIP-seq, CLIP-seq, RNA-seq and shRNA-seq data in K562 with BETA and SURF, we discovered a two-layer regulatory network system centered on these four DRBP-SFs, while proposing 3 possible regulatory models where DRBP-SFs can connect transcriptional regulatory network and alternative splicing regulatory network cooperatively in chronic myeloid leukemia. The exploration of the identified DRBP-SFs provides new ideas for studying DRBP and regulatory networks, holding promise for further mechanistic discoveries of the two-layer gene regulatory system which may play critical roles in the occurrence and development of CML.